PENGARUH KINERJA MAKRO EKONOMI TERHADAP KINERJA INDUSTRI DAN KINERJA KEUANGAN PERUSAHAAN SERTA RETURN SAHAM PERUSAHAAN PERBANKAN - Purnama, I Gusti Agung Kresna Surya; Wiksuana, I Gusti Bagus; Mustanda, I Ketut (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 1 Tahun 2013)
The purpose of this study is to investigate the influence macroeconomic performance on industry performance and company financial performance and stock returns the banking company in Indonesia Stock Exchange.The analysis technique is path analysis. The results of this research are the macroeconomic performance  and company financial performance are not significant positive effect on stock return, while industrial  performance is not significant negative effect on stock returns. Subsequent findings is that macroeconomic performance has a significant positive effect on industrial performance and no significant positive effect on company financial performance, while industrial performance is not significant negative effect on the company financial performance of banking companies in Indonesia Stock Exchange.
Keywords: stock return, macroeconomic performance, industry performance, company financial performance